Peran Green Education dalam Menanamkan Kesadaran Lingkungan Sejak PAUD - Istnain Alfajri Husain (Journal of Humanities, Social Sciences, and Education, 2025)
Green Education is an educational approach that emphasizes the importance of environmental preservation through a continuous learning process. At the Early Childhood Education (PAUD) level, Green Education has a strategic role in instilling values ​​of environmental concern from an early age. This literature study aims to examine the role of Green Education in shaping environmental awareness in PAUD children. The research method uses a literature review of various national and international journals, books, and relevant education policy documents. The results of the study show that the implementation of Green Education in PAUD is able to foster an attitude of love for the environment through a play approach, nature-based learning, family involvement, and the integration of ecopedagogy values ​​in the curriculum. In addition, teachers have an important role in shaping children's environmentally friendly behavior through role models and real activities. This article emphasizes that the formation of environmental awareness must begin as early as possible so that ecological values ​​are firmly embedded in children's characters. The five main aspects discussed include the introduction of environmental values, the role of teachers, family involvement, an environmentally friendly play approach, and the integration of a green curriculum. This study recommends the need for teacher training, green curriculum development, and synergy between schools, parents, and communities in order to build a generation that cares about environmental sustainability.